UPACARA PANGGIH TEMANTEN PERSPEKTIF âURF - Albanna, Hasan (The Indonesian Journal of Islamic Family Law, 2014)
Abstract: In Javanese wedding, the ritual of Panggih Temanten (the meeting of bride and groom) is the culmination of a wedding ceremony. This ritual unite the bride and groom for the first time in a marriage knot. Usually, the ceremony is conducted in the brideâs residence right after the ijab-qabul ceremony between the guardian of the bride and the groom. In Javanese tradition, there are several items to prepare for this Panggih Temanten Ceremony. There are gantal, golden bowl, kacar-kucur, chicken eggs and sindur cloth. Before the Panggih ceremony, pre-ceremony is conducted which include the groom offering Sanggan and coconut fruit to the parents of the bride as a symbol of redeeming the bride, changing the Kembar Mayang (coconut flower), throwing gantal as a symbol of love between the two, stepping on chicken eggs by the groom as a symbol of the readiness of the groom to become husband, and washing with water full of flower and sindur ceremony which symbolizes the unity between bride and groom. In Islamic perpectice, the Pangih Temanten ceremony is part of Ãºrf (tradition), which can be valid or void. The Panggih Temanten can be considered as valid tradition because of its resemblance with the concept of walÄ«mah in islam. Abstrak: Upacara Panggih temanten merupakan puncak upacara dari serangkain acara perkawinan. Upacara temu atau panggih temanten yaitu suatu upacara saat bertemunya pengantin putra dengan pengantin putri. Upacara ini diselenggarakanÂ  di keluarga perempuan sesaat setelah upacara ijab Kabul selesai. Beberapa hal yang harus dipersiapkan sebelum acara ini dilaksanakan adalah: gantal, bokor mas, kacar-kucur, telur ayam, kain sindur. Sebelum upacara panggih, ada beberapa rentetan upacara yang dilakukan, yaitu: 1. Menyerahkan Sanggan dan Cikal kepada ibu dan ayah mempelai wanita, serta menukar Kembar Mayang. 2. Bucalan Gantal. 3. Ngindak tigan lan wijik sekar setaman. 4. Pasang Garu. 5. Menerobos benang Lawe. 6. Upacara Sinduran. 7. Pangkon Timbang. 8. Kacar-Kucur. 9. Dhahar Kembul. 10. Sungkeman. 11. Resepsi Perkawinan. Dalam perpektif hukum Islam, upacara panggih temanten merupakan bagian dari âurf. Tradisi tersebut bisa dikategorikan dengan âurf sahÄ«h jika dilaksanakan dengan mengikuti ketentuan syariat Islam, dan menjadi âurf fÄsid jika tidak sesuai dengan ketentuan syariat Islam. Di antara upacara panggih temanten yang termasuk âurf sahÄ«h adalah upacara sumgkeman dan resepsi pernikahan yang sesuai dengan konsep walÄ«mah dalam Islam.